Importance of T lymphocytes in brain injury, immunodeficiency, and recovery after cerebral ischemia - Brait, Vanessa H (Nature Publishing Group, 2012)
Following an ischemic stroke, T lymphocytes become activated, infiltrate the brain, and appear to release cytokines and reactive oxygen species to contribute to early inflammation and brain injury. However, some subsets of T lymphocytes may be beneficial even in the early stages after a stroke, and recent evidence suggests that T lymphocytes can also contribute to the repair and regeneration of the brain at later stages. In the hours to days after stroke, T-lymphocyte numbers are then reduced in the blood and in secondary lymphoid organs as part of a ‘stroke-induced immunodeficiency syndrome,' which is mediated by hyperactivity of the sympathetic nervous system and the hypothalamic–pituitary–adrenal axis, resulting in increased risk of infectious complications. Whether or not poststroke T-lymphocyte activation occurs via an antigen-independent process, as opposed to a classical antigen-dependent process, is still controversial. Although considerable recent progress has been made, a better understanding of the roles of the different T-lymphocyte subpopulations and their temporal profile of damage versus repair will help to clarify whether T-lymphocyte targeting may be a viable poststroke therapy for clinical use.